Conceptual bases of formation of reflexive skills of students of pedagogical university in the process of independent educational activity (Pedagogy of Higher and Secondary Education, 2012)
Pitinak T. V. Conceptual bases of formation of reflexive skills of students of pedagogical university in the process of independent educational activity.The article illustrates the problem of the basic concepts of forming students’ reflexive abilities in Pedagogical University in the process of self-directed (independent) educational activity.
Keywords: reflection; abilities; reflexive abilities; self-directed (independ- ent) educational activity